2000
DOI: 10.1097/00006454-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis carinii pneumonia in South African children infected with human immunodeficiency virus

Abstract: PCP is an important pathogen in HIV-infected infants in South Africa and is associated with a high mortality. Induced sputum is effective for obtaining lower respiratory tract secretions for diagnosis of PCP but an NPA is not useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 23 publications
4
74
0
Order By: Relevance
“…[11] LDH has been suggested as a diagnostic test for PCP, with levels >500 IU/L taken as positive evidence. [6] Whilst not all the infants in this study had a LDH >500 IU/L, most did.…”
Section: Discussionmentioning
confidence: 99%
“…[11] LDH has been suggested as a diagnostic test for PCP, with levels >500 IU/L taken as positive evidence. [6] Whilst not all the infants in this study had a LDH >500 IU/L, most did.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no testing for Pneumocystis jirovecii or Mycobacterium tuberculosis, which would be expected to occur more frequently in HIV-infected children. [28][29][30] There are recent studies that also used molecular techniques to identify viral pathogens in lower respiratory infections (LRTI) in infants in sub-Saharan Africa, although they do not specifically report by infant HIV-infection and feeding strategy . [31][32][33][34][35][36][37][38] Several studies found that RSV was the most frequent pathogen, particularly in infants under 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocystis jirovecii is a significant cause of pneumonia (PCP) in HIV-infected children, especially in the absence of antiretroviral (ARV) therapy or prophylactic treatment (CPT), with high (28-63%) mortality rates [9][10][11][12][13][14][15]. The estimated risk of PCP among perinatally HIV-infected children during the first year of life ranges from 7% to 20% [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Younger age (< 1 year) is associated with increased risk of PCP, especially during the first six months of life [10,[15][16][17][18][20][21][22][23][24]. Studies from Africa reported PCP prevalence rates from 10% to 48.5% among HIV-infected children hospitalized with severe pneumonia [10][11][12]14,15]. Postmortem studies have shown that the prevalence of PCP among HIV-related deaths in children ranged from 11.5% to 52% [18,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%